Unprecedented photocatalytic conversion of gaseous and liquid CO2 on graphene-impregnated Pt/Cu-TiO2: The critical role of Cu dopant - Al Jitan, Samar; Li, Yuting; Bahamon, Daniel; Žerjav, Gregor; Tatiparthi, Vikram Sagar; Aubry, Cyril; Sinnokrot, Mutasem; Matouk, Zineb; Rajput, Nitul; Gutierrez, Monserrat; Al-Ali, Khalid; Hashaikeh, Raed; et al. (Journal of environmental chemical engineering, 2023)
In the context of sustainable development, the photocatalytic conversion of CO2 represents an appealing approach to mitigate climate change while also helping the economy. In this regard, numerous catalysts have been tested for the photoreduction of gaseous CO2; however, the photoconversion of pure liquid CO2 has rarely been investigated. This work provides a novel approach for the application of photocatalytic CO2 conversion through the utilization of CO2 in its pure liquid state. Experimental results show much higher CO yields during the photoreduction of liquid CO2 when compared to gaseous CO2. This is ascribed to stronger interactions between CO2 and TiO2 when considering the solvation effect, as confirmed by DFT calculations. Results also show the positive effect of doping TiO2 with copper. The CO yields obtained with liquid CO2, which range from ca. 92–206 mmol·gcat−1, are the highest ever reported. [Display omitted] •Liquid CO2 photoconversion is more favourable than gas CO2.•Doping TiO2 with copper has a positive effect on CO2 photoconversion.•Carbon monoxide, acetaldehyde, and formaldehyde can be obtained in very high yields.•The distance of CO2 to TiO2 surface decreases when considering solvation effect.